Children's physical activity and sedentary behavior is related between different parts of a day - Claudio R. Nigg; Chrissy Chard; Guangxiang Zhang; Carina Nigg (Bern Open Publishing, 2022)
It is unclear how different day parts are related to each other in terms of children's physical activity (PA) or sedentary behavior (SB) and how moderators (sex, weight status or age) affect this. As many health interventions aim to increase PA and decrease SB, knowledge about same-day PA and SB patterns is important and related to practical implications. Therefore, study aims were to identify: 1) children's PA and SB relationships between parts of a day; and 2) moderators of these relationships. Participants (n = 1,085; 50.14% female; mean age = 8.60 [SD = 1.75] years; mean BMI%ile = 61.31 [31.57] kg/m2) wore a GENEActiv accelerometer for six days. Correlations between school-day and out of school (after school plus evening) moderate-vigorous PA (MVPA) and SB percent were calculated. Analyses were further stratified by sex, weight status, and age. There were strong negative correlations between MVPA % in school with SB % in school (r = -0.92, p < 0.01) as well as between MVPA % out of school with SB % out of school (r = -0.94, p < 0.01). Moderate positive correlations were found between MVPA % in school with MVPA % out of school (r = 0.40, p < 0.01) as well as between SB % in school with SB % out of school (r = 0.39, p < 0.01). This was similar across sex, weight status and age. Children's PA and SB is related between different day parts, independent of sex, weight status and age. Thus, promoting more PA and less SB for children at any part of the day is likely to positively affect PA and SB at other day parts.